2004
DOI: 10.1038/ng1305
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression–based high-throughput screening(GE-HTS) and application to leukemia differentiation

Abstract: Chemical genomics involves generating large collections of small molecules and using them to modulate cellular states. Despite recent progress in the systematic synthesis of structurally diverse compounds, their use in screens of cellular circuitry is still an ad hoc process 1-4 . Here, we outline a general, efficient approach called gene expression-based highthroughput screening (GE-HTS) in which a gene expression signature is used as a surrogate for cellular states, and we describe its application in a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
216
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(220 citation statements)
references
References 22 publications
3
216
1
Order By: Relevance
“…Nitroblue tetrazolium (NBT) reduction also increased slightly but statistically significantly in U937T pool and U937T clone cell lines upon HIF-1a induction ( Figure 2c and data not shown). By the way, ATRA or vitamin D 3 treatment upregulated expressions of neutrophil cytosolic factor-1 (NCF1), interleukin-1 receptor antagonist (IL1RN), orosomucoid 1 (ORM1) and secreted phosphoprotein 1 (SPP1) in NB4 cells, four myeloid cell differentiation signatures recently identified (Stegmaier et al, 2004), while ATRA only increased NCF1 expression and vitamin D 3 raised expressions of other three markers except for SPP1 in U937 cells (Figure 2d). In U937T pool and U937T clone cell lines, HIF-1a induction significantly increased NCF1, SPP1 and IL1RN expression.…”
Section: Hif-1a Induction Triggers Differentiation With Growth Arrestmentioning
confidence: 88%
“…Nitroblue tetrazolium (NBT) reduction also increased slightly but statistically significantly in U937T pool and U937T clone cell lines upon HIF-1a induction ( Figure 2c and data not shown). By the way, ATRA or vitamin D 3 treatment upregulated expressions of neutrophil cytosolic factor-1 (NCF1), interleukin-1 receptor antagonist (IL1RN), orosomucoid 1 (ORM1) and secreted phosphoprotein 1 (SPP1) in NB4 cells, four myeloid cell differentiation signatures recently identified (Stegmaier et al, 2004), while ATRA only increased NCF1 expression and vitamin D 3 raised expressions of other three markers except for SPP1 in U937 cells (Figure 2d). In U937T pool and U937T clone cell lines, HIF-1a induction significantly increased NCF1, SPP1 and IL1RN expression.…”
Section: Hif-1a Induction Triggers Differentiation With Growth Arrestmentioning
confidence: 88%
“…We analyzed gene expression signatures of HL-60 cells treated with 1,25-dihydroxy Vitamin D3 (Vitamin D), PMA, and all-trans retinoic acid (Stegmaier et al, 2004), along with gene expression signatures of THP-1 cells treated with the BET bromodomain inhibitor JQ1 (Zuber et al, 2011), and MV4-11 and MOLM-13 cells treated with the DOT1L inhibitor EPZ004777 , compounds that cause AML differentiation and death. We identified a list of genes significantly down-regulated by the individual agents (fold change expression ≥ 1.5, P ≤ 0.05, Benjamini-Hochberg False Discovery Rate [FDR(BH)] ≤ 0.05) and found a core subset of 198 genes that were robustly downregulated across all five datasets based on the selection criteria mean fold change of expression ≥ 1.5 across all datasets and (ii) significant fold change of expression ≥ 1.5 (P ≤ 0.05, FDR(BH) ≤ 0.05) in at least four out of the five datasets ( Fig.…”
Section: Res Ults One-carbon Folate Metabolism Is a Core Pathway Altementioning
confidence: 99%
“…In addition, other miRNAs, including miR125b and miR-143, have been directly associated with the differentiation and proliferation of certain cell types (Esau et al, 2004;Lee et al, 2005). Finally, miRNA expression patterns may change when cells are treated with differentiation-promoting agents (Kasashima et al, 2004;Stegmaier et al, 2004), and recent studies have shown that undifferentiated human embryonic stem cells express certain miRNAs (Suh et al, 2004). Therefore, although it seems likely that downregulation of certain miRNAs may be a feature of tumor cells and de-differentiation, it remains to be seen whether miRNA expression changes are a cause or consequence of neoplasia.…”
Section: Mirnas and Cancermentioning
confidence: 99%